Media Puzzle as an Interactive Strategy to Enhance Arabic Vocabulary Mastery among Students: A Study in Class IV of MIN 1 Probolinggo. - Nur Asiah Jamilah; Mualim Wijaya (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The research is motivated by the students' low interest and limited vocabulary acquisition in Arabic, which are attributed to unengaging teaching methods and the minimal use of instructional media. This study aims to examine the effectiveness of using puzzle-based media in improving Arabic vocabulary mastery among fourth-grade students at MIN 1 Probolinggo. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation. The findings indicate that the implementation of puzzle media in Arabic instruction significantly enhances students’ vocabulary acquisition. The students demonstrated increased enthusiasm, active participation, and improved retention of new vocabulary due to the enjoyable and interactive nature of the learning process. Furthermore, the classroom environment became more conducive and collaborative, fostering student engagement in questioning and discussion. Thus, puzzle media is proven to be an effective alternative instructional tool for enhancing Arabic vocabulary mastery at the elementary school level.